Performance of care for end‐of‐life cancer patients in Tuscany: The interplay between place of care, aggressive treatments, opioids, and place of death. A retrospective cohort study. (17th April 2019) - Ferrè, Francesca; Vinci, Bruna; Murante, Anna Maria
Summary: Supportive and palliative care at the end of life (EOL) is a core component of health systems. Providing care at the EOL may require the interaction of several care providers working in different settings including nursing homes, home care, hospices, and hospitals. This work aims to (a) provide evidence on the performance of EOL care for cancer patients across healthcare organizations, with a focus on the place of care, aggressive treatments, opioids, and the place of death and (b) analyze factors associated with dying in hospital. A population‐based retrospective study was performed using administrative data from Tuscany region (Italy). Thirteen thousand sixty‐six cancer patients who died in 2016 were considered. There is a marked variability in EOL care within regional areas, with the multilevel logistic regression highlighting a greater likelihood of dying in hospital for patients who were admitted to intensive care units or previously hospitalized. There is a lower probability of dying in acute care setting for patients assisted in hospices and in both hospital and hospices/home care and for patients treated with opioids. This intraregional variation highlights the need to improve EOL planning and rethink the delivery of supportive/palliative care. Further investigations on the preferences of patients may lead to more understanding.